(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the use of films as a contextualized approach to English language teaching, emphasizing their role in improving language acquisition and cultural understanding. This approach not only promotes language development but also prepares students for practical communication in different contexts. The findings highlight the value of integrating film methods into language education to provide an integrated, multimodal learning experience that engages students of different learning styles.